Meningkatkan Minat dan Capaian Hasil Belajar Peserta Didik Melalui Penerapan Metode Pembelajaran Kooperatif KWL pada Mata Pelajaran Pendidikan Agama Katolik dan Budi Pekerti pada Siswa Kelas X-A SMA Negeri 1 Lahusa, Kabupaten Nias Selatan - Sarihati Harefa (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This class action research (PTK) was carried out on students in grade X-A SMA Negeri 1 Lahusa South Nias for the 2024/2025 academic year, due to problems, namely the low learning outcomes of Catholic Religious Education and Ethics subjects due to low student learning motivation. Through the application of the KWL cooperative learning method, this problem is tried to be improved and improved The stages in this study are carried out as many as two cycles, the steps in each cycle consist of four stages, namely the planning stage, the implementation of action (acting), observation (observing) and reflection (reflecting). In the observation section, observers and researchers collect data by observing the activities of students and teachers in the learning process through the use of mass media in Catholic Religious Education and ethics lessons. The results of the study show that during the learning process in cycle I it is 56% while in cycle II it is 87%. The increase in the two cycles is 30%. The application of the KWL Cooperative learning method was 31% in the criteria in the initial condition of being quite good to 66% in the first cycle and to 87% in the l very good criterion in the second cycle. From cycles I and II, students' interest in learning has reached 16.85% and has reached the success criteria. Based on the results of the research mentioned above, the KWL cooperative method can be applied in the learning of Catholic Religious Education and Ethics at SMA Negeri 1 Lahusa because it is proven to increase the learning interest of students in class X-A, especially in the KWL cooperative discussion material.